Updates in the skeletal and joint protective effects of tocotrienol: a mini review - Chin, Kok-Yong (Frontiers in Endocrinology, 2024)
Osteoporosis and osteoarthritis continue to pose significant challenges to the aging population, with limited preventive options and pharmacological treatments often accompanied by side effects. Amidst ongoing efforts to discover new therapeutic agents, tocotrienols (TTs) have emerged as potential candidates. Derived from annatto bean and palm oil, TTs have demonstrated efficacy in improving skeletal and joint health in numerous animal models of bone loss and osteoarthritis. Mechanistic studies suggest that TTs exert their effects through antioxidant, anti-inflammatory, Wnt-suppressive, and mevalonate-modulating mechanisms in bone, as well as through self-repair mechanisms in chondrocytes. However, human clinical trials in this field remain scarce. In conclusion, TTs hold promise as agents for preventing osteoporosis and osteoarthritis, pending further evidence from human clinical trials.